Monitoring of telomere dynamics in peripheral blood leukocytes in relation to colorectal cancer patients’ outcomes - Tomasova, Kristyna; Kroupa, Michal; Zinkova, Alzbeta; Korabecna, Marie; Vymetalkova, Veronika; Skrobanek, Pavel; Sojka, Ladislav; Levy, Miroslav; Hemminki, Kari; Liska, Vaclav; Hosek, Petr; Kumar, Rajiv; et al. (Frontiers in Oncology, 2022)
We investigated the possible associations between leukocyte telomere length, therapy outcomes, and clinicopathological features in patients with colorectal cancer. Additionally, telomerase reverse transcriptase (TERT) expression was evaluated. Telomere length was measured using singleplex qPCR in 478 consecutive leukocyte DNA samples from 198 patients. Blood was drawn at diagnosis prior to any therapy and then at 6-month intervals for 18 months. Following diagnosis, the telomeres gradually shortened during the course of the treatment regardless of the patient's age. The most pronounced decrease was observed 12 months after the diagnosis (p < 0.0001). Based on tumor localization, the decrease in telomere length one year after the diagnosis followed different trajectories (p = 0.03). In patients treated with adjuvant therapy, telomere length correlated with the time elapsed after completion of therapy (p = 0.03). TERT expression did not correlate with the telomere length; however, it was higher in women than men (1.35-fold, 95% CI 1.11–1.65, p = 0.003) and in smokers than non-smokers (1.27-fold, 95% CI 1.01–1.61, p = 0.04). Leukocyte telomere length declines naturally during aging, but the accelerated shortening observed in our patients was age-independent. Telomere length manifestly reflected chemotherapy impact and could be linked to therapy toxicity.